Combinatorial Proofs of Some Identities for Nonregular Continued Fractions. (29th September 2012) - Panprasitwech, Oranit
Abstract : A combinatorial interpretation of nonregular continued fractions is studied. Using a modification of a tiling technique due to Benjamin and Quinn, combinatorial proofs of some identities for nonregular continued fractions are obtained.